Pengaruh Motivasi Belanja Hedonis dan Promosi Penjualan terhadap Perilaku Impulse Buying Konsumen Marketplace Shopee Pada Generasi Z di Kota Singaraja - Apriani, Nyoman Devi; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2025)
This research aims to determine the influence of hedonic shopping motivation and sales promotions partially and simultaneously on the impulse buying behavior of Shopee marketplace consumers in generation Z in the city of Singaraja. This type of research is causal research with a quantitative approach. The population used is generation Z Shopee marketplace consumers in the city of Singaraja. The sampling used was an accidental sampling technique, so the sample used was 130 respondents. The type of data used is quantitative data and the data sources used are primary data sources and secondary data. Data collection methods use observation and questionnaire methods. Data processing uses the help of the Statistical Package for The Social Science (SPSS) version 27 program. The data analysis technique used is multiple linear regression analysis with partial (t test) and simultaneous (F test) hypothesis testing. The results of this research show that (1) hedonic shopping motivation has a partially positive and significant effect on the impulse buying behavior of Shopee marketplace consumers in generation Z in the city of Singaraja, (2) sales promotions have a partially positive and significant effect on the impulse buying behavior of Shopee marketplace consumers in generation Z in the city of Singaraja, and (3) hedonic shopping motivation and sales promotions simultaneously have a positive and significant effect on the impulse buying behavior of Shopee marketplace consumers in generation Z in the city of Singaraja.